Association of matrix metalloproteinase-1, 9, 12 and tissue inhibitor of metalloproteinase-1 gene polymorphisms in malay male essential hypertensive subject - Tabatabaee, Farizeh Aalam Ghomi (2015)
Genetic polymorphisms are the modified sequences of the DNA and they serve as molecular biomarkers for the detection of the individual at risk of developing the disease. Essential hypertension (EH) are majority of hypertensive cases and diagnosed where there is no clear evidence of medical condition predisposing to the high BP. There have been variety of the genetic studies in relation to hypertension and some of them showed association with occurrence of hypertension. Family of the matrix metalloproteinases (MMP) belong to the large family of the zinc-dependent endopeptidases that are involved in many physiological disorders ranging from cancer to cardiovascular disorders. Matrix metalloproteinases are implicated in degradation of the extracellular matrix (ECM) which is fundamental in many aspects, both physiologically and pathologically. These include: normal functioning of the cells from development to growth and proliferation, as well as pathological conditions such as cardiac remodeling and cancer development. Matrix metalloproteinases play important role in hypertensive vascular stiffness, remodeling and dysfunction. They may be involved in the excessive degradation of ECM components, vascular smooth muscle cells migration and proliferation and intima layer invasion by monocytes. Besides,ECM remodeling is largely determined by the balance of MMPs with respect to tissue inhibitor of metalloproteinases (TIMP). Several studies have been reported the imbalanced MMP:TIMP-1 ratio in hypertensive subjects, indicating the depressed systematic degradation of collagenase in etiology of hypertension. The main objective of this study was to determine the candidate gene polymorphisms involved in ECM metabolism among Malaysian male subject with EH. Since, there have been variety of genetic association studies of MMPs and TIMPs conducted on different populations,but no study was done on Malaysian populations and in relation to hypertension. A total of 133 newly diagnosed EH subjects and 129 unrelated healthy individuals were requited under this study. The genomic DNA of these individuals were extracted from buffy coat and the plasma was separated for biochemical analysis. The genotyping of the polymorphisms were done by polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP) method. The PCR product and the restricted fragment product were run on agarose gel electrophoresis. All the statistical analysis were done by using Statistical Package for the Social Sciences (SPSS) version no. 21.0. The demographic characteristic of the subjects such as age, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), low density lipoprotein (LDL), triglyceride (TG) and cholesterol (Chol) were shown to be differentially significant (p 0.05) in case subjects when compared to the controls, high density lipoprotein (HDL) did not show any significance. The genotype and allelic distribution of TIMP-1 372 T/C polymorphism was highly significant in hypertensive subjects as compared to the controls (p 0.05). Whilst, SNPs in position -1607 (1G/2G) in the MMP-1 gene, position -1562 (C/T) and 279 (R/Q) of the MMP-9 gene as well as site -82 (A/G) in the MMP-12 gene did not differ significantly (p 0.05) when compared to the controls. However, the data showed that the SNP in TIMP- 1 gene at site 372 (T/C) was associated with EH in Malay male hypertensive subjects. Hence, the allele and genotype of TIMP-1 polymorphisms may be considered as a possible genetic biomarker and a risk factor for EH.